Integrative Strategies for Malaria Elimination: The Role of Surveillance, Vector Control, and Community Engagement - Rau, Muhammad Jusman (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2023)
Malaria remains a major public health concern in many regions, despite global efforts toward its elimination. This study systematically reviews malaria elimination strategies, emphasizing the role of surveillance, vector control, and community based interventions. Using a comprehensive literature review, data from PubMed, Scopus, and Web of Science were analyzed to assess epidemiological trends, intervention effectiveness, and persisting challenges. Findings indicate that active surveillance programs and integrated vector control measures have significantly contributed to malaria reduction in countries such as China, El Salvador, and Rwanda. However, human mobility, climate variability, and drug resistance continue to pose challenges, particularly in malaria endemic regions. To address these barriers, the study underscores the necessity of strengthening health systems, enhancing cross border collaborations, and leveraging emerging technologies for real time disease monitoring. Policymakers must tailor interventions based on regional epidemiological patterns and promote greater community engagement in malaria control efforts. Future research should focus on refining stratification models, assessing novel vector control strategies, and examining the long term sustainability of malaria elimination initiatives. By implementing targeted, evidence based approaches, malaria elimination can be accelerated, bringing the world closer to the goal of eradication.